Metodologias Cri-Ativas em Artes: experiências em aulas de performance na PUC/SP - Brandão, Samira de Souza (2021)
In this doctoral research we investigate some questions about active methodologies in higher education in Arts, especially its uses in the performance and theatrical language; and how these methodologies are widely used in the performance classroom, having the student-artist as the center of the learning process. In order to do this, we approach the pioneering work of the theater director and professor Renato Cohen (1956-2003), with whom we started this research. Based on our long experience as an artist and teacher in the Bachelor's Degree in Communication and Arts of the Body at PUC/SP, especially in performance disciplines, we defend, in this thesis, the concept of Cre-Active Methodologies in the teaching of Arts, elaborating, through action research, a series of psychophysical training practices and activities created from this methodology, and sharing the knowledge that was generated in these experiments, proposing an innovative approach in the process of teaching-learning in Arts